Elimination of thinning practices on cotton crop - Cia, Edivaldo; Júnior, Enes Furiani; Sabino, Nelson Paulieri; Fuzatto, Milton Geraldo; Ferraz, Carlos Antonio Menezes; Carvalho, Luiz Henrique; Bortoetto, Nelson; Sabino, José Carlos; Campana, Mario pércio (Pesquisa Agropecuaria Brasileira, 2001)
This work was developed during the agricultural years of 1979/80 to 1982/83 in different localities in the State of São Paulo, Brazil, to evaluate the effect of plant thinning in the cotton plantation. The trial was carried out in a randomized block design and in a factorial scheme with six treatments and six replicates. The treatments consisted of 12 and 24 seeds/m submitted to mechanical delinting + fungicide, and chemical delinting + fungicides. For evaluation of the results, two conjunct analyses were done based on the plant emergence: normal emergence and late emergence, by studying the following traits: emergence, production, final stand, boll weight, seed weight and fiber index. The results showed that under adverse conditions to germination a low emergence occurred, causing smaller plant population and consequently lesser cotton production. With greater stand, smaller boll weight, seed weight, and minor percentage and index of fiber occurred. It was evidenced that the viability of eliminating the plant population thinning by seed treatment with fungicides and chemical delinting exists, since their planting be done under good environment conditions for germination.